2012
DOI: 10.1002/uog.12270
|View full text |Cite
|
Sign up to set email alerts
|

Risk of epithelial ovarian cancer in asymptomatic women with ultrasound‐detected ovarian masses: a prospective cohort study within the UK collaborative trial of ovarian cancer screening (UKCTOCS)

Abstract: Objective To estimate the risk of primary epithelial ovarian cancer (EOC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 22 publications
1
64
1
5
Order By: Relevance
“…Due to the potential morbidity of surgical treatments, clinical monitoring may be recommended since a large proportion of these cysts are associated with low risk for developing ovarian cancer 1,24 (B).…”
Section: Good Practices In Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the potential morbidity of surgical treatments, clinical monitoring may be recommended since a large proportion of these cysts are associated with low risk for developing ovarian cancer 1,24 (B).…”
Section: Good Practices In Treatmentmentioning
confidence: 99%
“…Due to the wide use of pelvic and transvaginal ultrasound for routine gynecological evaluation, during the reproductive years and after menopause, the incidental finding of adnexal masses has been observed in a growing proportion of women, leading to discussions on the approach to be used in asymptomatic patients 1 (B). One of the main concerns of the gynecologist is the identification of risk markers for the development of ovarian cancer, which may lead to early surgical treatment and prevent progression of the disease during the expectant conservative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the higher prevalence of Type II EOC, the risk of borderline or type I cancer in women with ultrasound abnormalities seems to be higher than does the risk of type II cancer. This has important immediate implications for patients with incidental adnexal findings as well as for any future ultrasound-based screening [19].…”
Section: Adenocarcinomamentioning
confidence: 99%
“…[3][4][5] Malignancy has been found in apparently stable masses that eventually enlarged and increased in morphologic complexity in up to 3 years after initial detection. 6 These results gleaned from 11,982 ultrasound examinations define the risks from terminating ultrasound surveillance. 6 We have used the definition of acceptable risk level from environmental studies of no more than 1 extra death per 100,000 deaths to normalize the reported data.…”
mentioning
confidence: 98%
“…6 These results gleaned from 11,982 ultrasound examinations define the risks from terminating ultrasound surveillance. 6 We have used the definition of acceptable risk level from environmental studies of no more than 1 extra death per 100,000 deaths to normalize the reported data. 7 The absolute risks calculated from the United Kingdom Collaborative Trial of Ovarian Cancer Screening trial data for the appearance of malignancy in up to 3 years after an initial ultrasound examination are considerably elevated ( Figure 2).…”
mentioning
confidence: 98%